Nitrogen-doped magnetic carbon aerogel wave-absorbing material with bionic coralline microstructure and preparation method of nitrogen-doped magnetic carbon aerogel wave-absorbing material
Through water-induced Ni-MOF self-assembly and freeze-drying carbonization technology, nitrogen-doped magnetic carbon aerogel absorbing materials with bionic coral-like microstructure were prepared, which solved the problems of low mechanical strength and insufficient electromagnetic wave absorption performance of existing magnetic metal/carbon composite materials, and achieved efficient electromagnetic wave absorption effect.
Patent Information
- Application Number
- CN202411823294.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-28
AI Technical Summary
The existing magnetic metal/carbon composite materials exist in powder form, have low mechanical strength and poor integrity, which limit their application in practice, and the electromagnetic wave absorption performance of carbon-based aerogels is insufficient.
Nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure was prepared by water-induced Ni-MOF self-assembly, freeze-drying and carbonization. The material has a three-dimensional porous structure macroscopically and a bionic coral-like structure microscopically. Combined with nitrogen doping and magnetic nickel nanoparticles, it enhances the electromagnetic wave absorption performance of the material.
The maximum reflection loss value of this material at a thickness of 2.02mm is -64.40dB, and the effective absorption bandwidth reaches 4.8GHz, showing excellent electromagnetic wave absorption capacity.
Smart Images

Figure CN119706788A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a wave absorbing material, in particular to a nitrogen-doped magnetic carbon aerogel wave absorbing material with a bionic coral-like microstructure and a preparation method thereof. Background Art
[0002] Metal-organic frameworks (MOFs) are formed by transition metal ions and organic groups bound by covalent coordination bonds. Magnetic metal / carbon composites obtained by carbonizing MOFs have received widespread attention in the past few years because the periodic arrangement of organic ligands and metal nodes in crystalline MOFs lays a good foundation for the uniform dispersion of metal nanoparticles throughout the carbon matrix, and the properties of MOF derivatives also meet the design requirements of magnetic metal / carbon composites as high-performance electromagnetic wave absorption materials; however, existing MOF-derived magnetic metal / carbon composites usually exist in powder form, with problems of low mechanical strength and poor integrity, which limits their application in practice and prevents them from being widely promoted and applied.
[0003] Biomass carbon aerogel has become one of the most promising electromagnetic wave absorption materials in recent years due to its high porosity, large specific surface area and rich functional groups, which can provide multiple interfaces and polarization sites for the effective attenuation of electromagnetic waves. However, due to its high electrical conductivity and impedance mismatch caused by single loss, the wave absorption performance of carbon-based aerogel still cannot meet practical requirements. However, it is worth noting that magnetic elements can give carbon-based aerogels suitable impedance matching and synergistic magnetic losses.
[0004] In view of the fact that structure and composition are the two main factors that restrict the performance of electromagnetic wave absorbing materials, the reasonable design of the structure of electromagnetic wave absorbing materials can help improve the attenuation capacity of electromagnetic wave absorbing materials. Common electromagnetic wave absorbing materials have porous structures, flower-like structures, yolk-shell structures, hollow structures and bionic micro-nano structures. These unique microstructures can not only reduce the density of microwave absorbers and improve their impedance matching, but also provide rich interfaces and dipole polarization, increasing multiple reflections and scattering of electromagnetic waves.
[0005] Therefore, introducing micro-nanoscale microstructures into three-dimensional carbon aerogels to construct new magnetic metal / carbon aerogel absorbers is a promising design strategy. However, there is no method to fully integrate MOF conversion, micro-nanostructures and aerogel structures to construct magnetic metal / carbon aerogel absorbers. Summary of the invention
[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure and a preparation method thereof. The prepared nitrogen-doped magnetic carbon aerogel absorbing material has excellent electromagnetic wave absorption performance.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for preparing a nitrogen-doped magnetic carbon aerogel absorbing material having a bionic coral-like microstructure comprises the following steps:
[0009] Step 1, dissolving 1.5-2.5g of nickel salt and 1.0-2.0g of organic ligand in 20-30mL of N,N-dimethylformamide, stirring and ultrasonicating in sequence at room temperature to mix them evenly, reacting at 130-150°C for 2-3h, and then filtering, washing and drying in sequence to obtain a green powder;
[0010] Step 2, firstly mix anhydrous ethanol and water in a volume ratio of 1: (5-10) to obtain an ethanol solution, then disperse 3-5 g of green powder in 25-30 mL of ethanol solution to obtain solution B, then add nitrogen source to solution B in a mass ratio of green powder to nitrogen source (1-4): 1, ultrasonically disperse, let stand, then collect the precipitate, freeze-dry, and obtain aerogel;
[0011] Step 3: Place the aerogel in a crucible and place it in a muffle furnace. In an argon atmosphere, heat the aerogel from room temperature to 600-800°C at a heating rate of 5-10°C / min for 2-3 hours to obtain a nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure.
[0012] Furthermore, the nickel salt in step 1 is nickel nitrate hexahydrate, nickel chloride hexahydrate or nickel acetate tetrahydrate.
[0013] Furthermore, the organic ligand in step 1 is 1,3,5-benzenetricarboxylic acid or 2,5-dihydroxyterephthalic acid.
[0014] Furthermore, the ultrasonic time in step 1 is 20 to 30 minutes.
[0015] Furthermore, the nitrogen source in step 2 is chitosan, gelatin, collagen or soy protein.
[0016] Furthermore, the ultrasonic dispersion time in step 2 is 10 to 30 minutes.
[0017] Furthermore, the standing time in step 2 is 12 to 48 hours.
[0018] A nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure has a macroscopic three-dimensional porous structure and a microscopic bionic coral-like microstructure.
[0019] Furthermore, the bionic coral-like microstructure contains a yolk-shell Ni / C structure.
[0020] Compared with the prior art, the present invention has the following technical effects:
[0021] The present invention firstly induces Ni-MOF self-assembly through water, and then freeze-dries and carbonizes it to prepare a nitrogen-doped magnetic carbon aerogel absorbing material. On the one hand, it has a macroscopic three-dimensional porous structure and a bionic coral-like microstructure, which can extend the transmission path of electromagnetic waves, promote multiple reflections and scattering of electromagnetic waves incident into the material, and then enhance conductivity loss and energy dissipation, and has excellent electromagnetic wave absorption performance; on the other hand, nitrogen doping can cause lattice defects, promote dipole polarization, reduce the reflection of electromagnetic waves by the material, increase the number of electromagnetic waves incident into the material, and help better absorb and attenuate the incident electromagnetic waves, thereby converting electromagnetic waves into heat, playing a role. Good dissipation effect reduces the projection of electromagnetic waves, thereby improving the absorbing performance of the material; on the other hand, the introduction of magnetic nickel nanoparticles increases the magnetic loss of the absorbing material, so that the nitrogen-doped magnetic carbon aerogel absorbing material produces a magnetic-dielectric synergistic effect, thereby significantly improving the absorbing effect; therefore, the nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure prepared by the present invention has a maximum reflection loss value of -64.40 dB at a thickness of 2.02 mm, an absorption bandwidth of 11.54-16.34 GHz for electromagnetic waves at a thickness of 1.82 mm, and an effective absorption bandwidth of 4.8 GHz, showing excellent electromagnetic wave absorption capacity.
[0022] A large number of egg yolk shell Ni / C structures exist in the bionic coral-like microstructure of the nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure prepared by the present invention. The egg yolk shell Ni / C structure can provide a large number of heterogeneous interfaces, resulting in the accumulation of free electrons at the contact points to form interface polarization, which is beneficial to the dissipation of electromagnetic waves, and further improves the absorption performance of the nitrogen-doped magnetic carbon aerogel absorbing material to electromagnetic waves. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : SEM image of the nitrogen-doped magnetic carbon aerogel absorbing material prepared in Example 2 of the present invention;
[0024] Figure 2 : TEM image of the nitrogen-doped magnetic carbon aerogel absorbing material prepared in Example 2 of the present invention;
[0025] Figure 3 : XRD pattern of the nitrogen-doped magnetic carbon aerogel absorbing material prepared in Example 2 of the present invention;
[0026] Figure 4 : Magnetic hysteresis loop diagram of the nitrogen-doped magnetic carbon aerogel absorbing material prepared in Example 2 of the present invention;
[0027] Figure 5(a) to Figure 5(c): Wave absorbing performance diagram of the nitrogen-doped magnetic carbon aerogel absorbing material prepared in Example 2 of the present invention;
[0028] Figure 6(a) to Figure 6(c) : Wave absorbing performance diagram of the nitrogen-doped magnetic carbon aerogel absorbing material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0030] Example 1
[0031] Step 1: 1.8 g of nickel nitrate hexahydrate and 1.3 g of 1,3,5-benzenetricarboxylic acid were placed in 30 mL of N,N-dimethylformamide, stirred at room temperature, and then ultrasonicated for 30 min to mix them evenly, reacted at 150° C. for 3 h, and then filtered, washed and dried in sequence to obtain a green powder;
[0032] Step 2: firstly mix anhydrous ethanol and water in a volume ratio of 1:7 to obtain an ethanol solution, then disperse 3 g of green powder in 25 mL of ethanol solution to obtain solution B, then add chitosan to solution B in a mass ratio of green powder to chitosan of 1:1, first ultrasonically disperse for 10 min, then stand for 12 h, then collect the precipitate, freeze-dry, and obtain aerogel;
[0033] Step 3: Place the aerogel in a crucible and place it in a muffle furnace. In an argon atmosphere, heat the temperature from room temperature to 600°C at a heating rate of 5°C / min for 2 hours to obtain a nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure.
[0034] from Figures 6(a) to 6(c) It can be seen that the nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure prepared in Example 1 has a maximum reflection loss value of -64.40 dB at a thickness of 2.02 mm, an absorption bandwidth of electromagnetic waves at a thickness of 1.82 mm of 11.54-16.34 GHz, and an effective absorption bandwidth of 4.8 GHz, indicating that the nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure prepared in Example 1 has excellent electromagnetic wave absorption capacity.
[0035] Example 2
[0036] Step 1: 2.0 g of nickel chloride hexahydrate and 1.5 g of 1,3,5-benzenetricarboxylic acid were added to 30 mL of N,N-dimethylformamide, stirred at room temperature, and then ultrasonicated for 30 min to mix them evenly, reacted at 150° C. for 3 h, and then filtered, washed and dried in sequence to obtain a green powder;
[0037] Step 2: firstly mix anhydrous ethanol and water in a volume ratio of 1:10 to obtain an ethanol solution, then disperse 4 g of green powder in 30 mL of ethanol solution to obtain solution B, then add gelatin to solution B in a mass ratio of green powder to gelatin of 2:1, firstly ultrasonically disperse for 20 min, then stand for 12 h, then collect the precipitate, freeze-dry, and obtain aerogel;
[0038] Step 3: Place the aerogel in a crucible and place it in a muffle furnace. In an argon atmosphere, heat the aerogel from room temperature to 700°C at a heating rate of 5°C / min for 2 hours to obtain a nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure.
[0039] from Figure 1 It can be seen that the microstructure of the nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure prepared in Example 2 is bionic coral-like, which is beneficial to extend the transmission path of the electromagnetic wave and promote multiple reflections and scattering of the incident electromagnetic wave.
[0040] from Figure 2 It can be seen that there are a large number of yolk shell Ni / C structures in the bionic coral-like microstructure of the nitrogen-doped magnetic carbon aerogel absorbing material with bionic coral-like microstructure prepared in Example 2, which can provide a large number of heterogeneous interfaces, resulting in the accumulation of free electrons at the contact point to form interface polarization, which is beneficial to the dissipation of electromagnetic waves.
[0041] from Figure 3 It can be seen that the nitrogen-doped magnetic carbon aerogel absorbing material with bionic coral-like microstructure prepared in Example 2 has three obvious diffraction peaks at 2θ of 44.5°, 51.8° and 76.4°, corresponding to the (111), (200) and (220) planes of metal Ni (JCPDS No. 04-0850), respectively, verifying that Ni 2+ It is completely reduced to metallic Ni during high-temperature pyrolysis.
[0042] from Figure 4 It can be seen that the nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure prepared in Example 2 shows ferromagnetism. The source of ferromagnetism benefits from the introduction of metal Ni. The metal Ni nanoparticles increase the magnetic loss of the absorbing material and can promote the nitrogen-doped magnetic carbon aerogel absorbing material to produce magnetic-dielectric synergy.
[0043] from Figures 5(a) to 5(c)It can be seen that the nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure prepared in Example 2 has a maximum reflection loss value of -25.10 dB at a thickness of 1.20 mm, an absorption bandwidth of electromagnetic waves at a thickness of 1.38 mm of 12.80-16.94 GHz, and an effective absorption bandwidth of 4.14 GHz, indicating that the nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure prepared in Example 2 has excellent electromagnetic wave absorption capacity.
[0044] Example 3
[0045] Step 1, 2.5 g of nickel chloride hexahydrate and 2.0 g of 2,5-dihydroxyterephthalic acid were added to 25 mL of N,N-dimethylformamide, stirred at room temperature, and then ultrasonicated for 25 min to mix them evenly, reacted at 140 ° C for 2 h, and then filtered, washed and dried in sequence to obtain a green powder;
[0046] Step 2: firstly mix anhydrous ethanol and water in a volume ratio of 1:8 to obtain an ethanol solution, then disperse 5 g of green powder in 27.5 mL of ethanol solution to obtain solution B, then take collagen and add it to solution B in a mass ratio of green powder to collagen of 3:1, firstly ultrasonically disperse for 30 min, then stand for 24 h, then collect the precipitate, freeze-dry it, and obtain aerogel;
[0047] Step 3: Place the aerogel in a crucible and place it in a muffle furnace. In an argon atmosphere, heat the temperature from room temperature to 800°C at a heating rate of 8°C / min for 2.5 hours to obtain a nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure.
[0048] Example 4
[0049] Step 1: 1.5 g of nickel acetate tetrahydrate and 1.0 g of 2,5-dihydroxyterephthalic acid were stirred in 20 mL of N,N-dimethylformamide at room temperature, and then ultrasonicated for 20 min to mix them evenly. The mixture was reacted at 130° C. for 2.5 h, and then filtered, washed and dried in sequence to obtain a green powder.
[0050] Step 2: firstly mix anhydrous ethanol and water in a volume ratio of 1:5 to obtain an ethanol solution, then disperse 3 g of green powder in 25 mL of ethanol solution to obtain solution B, then take collagen and add it to solution B in a mass ratio of green powder to collagen of 4:1, firstly ultrasonically disperse for 15 minutes, then stand for 48 hours, then collect the precipitate, freeze-dry it, and obtain aerogel;
[0051] Step 3: Place the aerogel in a crucible and place it in a muffle furnace. In an argon atmosphere, heat the temperature from room temperature to 800°C at a heating rate of 10°C / min for 3 hours to obtain a nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure.
[0052] Example 5
[0053] Step 1: 2.3 g of nickel acetate tetrahydrate and 1.8 g of 1,3,5-benzenetricarboxylic acid were added to 25 mL of N,N-dimethylformamide, stirred at room temperature, and then ultrasonicated for 20 min to mix them evenly, reacted at 130 ° C for 3 h, and then filtered, washed and dried in sequence to obtain a green powder;
[0054] Step 2: firstly mix anhydrous ethanol and water in a volume ratio of 1:6 to obtain an ethanol solution, then disperse 4 g of green powder in 30 mL of ethanol solution to obtain solution B, then take collagen and add it to solution B in a mass ratio of green powder to collagen of 2.5:1, firstly ultrasonically disperse it for 25 minutes, then let it stand for 36 hours, then collect the precipitate, freeze-dry it, and obtain aerogel;
[0055] Step 3: Place the aerogel in a crucible and place it in a muffle furnace. In an argon atmosphere, heat the temperature from room temperature to 700°C at a heating rate of 7°C / min for 2.5 hours to obtain a nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure.
Claims
1. A method for preparing a nitrogen-doped magnetic carbon aerogel absorbing material having a bionic coral-like microstructure, characterized in that: The steps include: Step 1, dissolving 1.5-2.5g of nickel salt and 1.0-2.0g of organic ligand in 20-30mL of N,N-dimethylformamide, stirring and ultrasonicating in sequence at room temperature to mix them evenly, reacting at 130-150°C for 2-3h, and then filtering, washing and drying in sequence to obtain a green powder; Step 2, firstly mix anhydrous ethanol and water in a volume ratio of 1: (5-10) to obtain an ethanol solution, then disperse 3-5 g of green powder in 25-30 mL of ethanol solution to obtain solution B, then add nitrogen source to solution B in a mass ratio of green powder to nitrogen source (1-4): 1, ultrasonically disperse, let stand, then collect the precipitate, freeze-dry, and obtain aerogel; Step 3: Place the aerogel in a crucible and place it in a muffle furnace. In an argon atmosphere, heat the aerogel from room temperature to 600-800°C at a heating rate of 5-10°C / min for 2-3 hours to obtain a nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure.
2. The method for preparing the nitrogen-doped magnetic carbon aerogel absorbing material having a bionic coral-like microstructure according to claim 1, characterized in that: The nickel salt in step 1 is nickel nitrate hexahydrate, nickel chloride hexahydrate or nickel acetate tetrahydrate.
3. The method for preparing the nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure according to claim 1, characterized in that: The organic ligand in step 1 is 1,3,5-benzenetricarboxylic acid or 2,5-dihydroxyterephthalic acid.
4. The method for preparing the nitrogen-doped magnetic carbon aerogel absorbing material having a bionic coral-like microstructure according to claim 1, characterized in that: The ultrasonic time of step 1 is 20 to 30 minutes.
5. The method for preparing the nitrogen-doped magnetic carbon aerogel absorbing material having a bionic coral-like microstructure according to claim 1, characterized in that: The nitrogen source in step 2 is chitosan, gelatin, collagen or soy protein.
6. The method for preparing the nitrogen-doped magnetic carbon aerogel absorbing material having a bionic coral-like microstructure according to claim 1, characterized in that: The ultrasonic dispersion time in step 2 is 10 to 30 minutes.
7. The method for preparing the nitrogen-doped magnetic carbon aerogel absorbing material with a bionic coral-like microstructure according to claim 1, characterized in that: The standing time in step 2 is 12 to 48 hours.
8. The nitrogen-doped magnetic carbon aerogel absorbing material having a bionic coral-like microstructure prepared by the method according to any one of claims 1 to 7, characterized in that: It has a macroscopic three-dimensional porous structure and a microscopic bionic coral-like microstructure.
9. The bionic coral-like microstructured nitrogen-doped magnetic carbon aerogel absorbing material according to claim 8, characterized in that: The bionic coral-like microstructure has an egg yolk-shell Ni / C structure.